Controlled synthesis and facets-dependent photocatalysis of TiO2 nanocrystals. (5th March 2015) - Roy, Nitish; Park, Yohan; Sohn, Youngku; Pradhan, Debabrata
Abstract: Titanium dioxide (TiO2 ) is a wide band gap semiconductor that has been extensively used in several environmental applications including degradation of organic hazardous chemicals, water splitting to generate hydrogen, dye sensitized solar cells, self cleaning agents, and pigments. Herein we demonstrate the synthesis of TiO2 nanocrystals (NCs) with the shapes of ellipsoids, rods, cuboids, and sheets with different exposed facets using a noncorrosive and nontoxic chemical (i.e. diethanolamine) as the shape controlling agent, unlike hydrofluoric acid commonly used. The TiO2 NCs of diverse shapes with different exposed facets were tested for photocatalytic hydroxyl radical (OH ) formation, which determines their photocatalytic behavior and the results were compared with the standard P-25 Degussa. The formation rate of OH per specific surface area was found to be >6 fold higher for rod-shaped TiO2 NCs than that of commercial Degussa P25 catalyst. The highest photocatalytic activity of rod-shaped TiO2 NCs is ascribed to the unique chemical environment of 010 exposed facets which facilitates the electron/hole separation in presence of 101 facets.